PENGGUNAAN ECENG GONDOK (Eichornia crassipes Solm.) DAN TEMPURUNG KELAPA DALAM PEMBUATAN BRIKET SEBAGAI POTENSI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOTEKNOLOGI KONVENSIONAL DI SMA - Rio Rasdian Saputra; Imam Mahadi; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the best composition of water hyacinth and coconut shell in making briquettes. This study was conducted from January to April 2017. The results were used as the design of the conventional biotechnology student worksheet in Senior High School. This research was conducted with 2 stages, first stage of making of briquettes mixture of water hyacinth and coconut shell in the Mechanical Engineering Production Laboratory of the University of Riau using RAL consisting of 7 treatments and 3 replications. Second, the design stage of the student worksheet use the learning model ADDIE (Analyze, Design, Development, Implementation and Evaluation) which only until the design stage. The making of briquettes mixture water hyacinth and coconut shell consists of raw material preparation stage, stage of carbonization, stage size reduction, briquette dough making stage, and briquette printing stage. Parameters in this research are water content, ash content, calorific value, density, and firmness of pressure. From the result of research got that treatment with ratio 1: 4 (B3) is the best treatment in making briquettes mixture water hyacinth and coconut shell. The results are then designed as conventional biotechnology student worksheet in Senior High School.Keywords : Water Hyacinth, Coconut Shell, Briquette, Student Worksheet, Biotechnology